2018
DOI: 10.1177/1362361318794179
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in food consumption and nutritional intake between children with autism spectrum disorders and typically developing children: A meta-analysis

Abstract: Children with autism spectrum disorders show higher food selectivity, which restricts consumption of some foods and may cause nutritional deficiencies. The aims of this meta-analysis are to determine the overall differences in nutritional intake and food consumption between children with autism spectrum disorder and control (typical development) children, as well as determine the extent to which the nutritional intake and food consumption of autistic children comply with the dietary recommendations. Children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 62 publications
(97 reference statements)
4
66
3
2
Order By: Relevance
“…In the most recent meta-analysis of 19 studies [ 10 ], Esteban-Figuerola et al (2019) also found that children with ASD consumed less protein, calcium, phosphorus, vitamin B2, and vitamin B12 than those without ASD. However, children with ASD consumed the same amount of carbohydrates, fat, magnesium, iron, zinc, retinol, folic acid, and pantothenic acid as typically developing children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the most recent meta-analysis of 19 studies [ 10 ], Esteban-Figuerola et al (2019) also found that children with ASD consumed less protein, calcium, phosphorus, vitamin B2, and vitamin B12 than those without ASD. However, children with ASD consumed the same amount of carbohydrates, fat, magnesium, iron, zinc, retinol, folic acid, and pantothenic acid as typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing evidence for the relationship between ASD and food selectivity in children [ 8 , 9 ], limited information is currently available on the relationship between ASD and nutrient intake. Previous studies compared the nutrient intake of ASD children and typically developing children [ 8 , 10 ]. A recent review reported inconsistencies in the extent and type of nutrient intakes; however, limited macronutrient and micronutrient intakes have been increasingly reported among children with ASD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified that children with ASD have low fruit and vegetable intake (Chistol et al 2018;Emond et al 2010;Marshall et al 2014;Schreck et al 2004;Sharp et al 2013), and we identified low citrus intake specifically in those with higher autistic-like traits. However, some studies have found that children with ASD eat more fruit than those without ASD (Esteban-Figuerola et al 2019;Herndon et al 2009), while other studies reported no difference in fruit and vegetable (Cohen, 1988) Autism Spectrum Quotient (AQ): measures autistic-like traits in the general population and ranges from 0 to 50. A higher score indicates more autistic-like traits.…”
Section: Discussionmentioning
confidence: 99%
“…Selective children with ASD often prefer foods with low nutritional value and high in fat, salt, and sugar [19]. Children with ASD were shown to have a lower protein intake, and their diets may be low in micronutrients [47,48]. Food variety has been shown to be a predictor of nutritional status of children with ASD [49].…”
Section: Food Selectivity and Mealtime Problemsmentioning
confidence: 99%